Letter (copy) : Goods for Northern Spain
029-0125-001 EXPORT/ST/MM.EAB/EKK/458. 9165 International. 19th June, 1937. Mr. S. Topping, The Co-operative Wholesale Society Ltd, Export Department, 1, Balloon Street, MANCHESTER. 4. Dear Mr. Topping, GOODS FOR NORTHERN SPAIN. With reference to our telephone conversation this morning with regard to the sending of goods for Northern Spain, we have to-day learned from the Agents Messrs. J.A. Billmeir & Co., that the steamer which will be taking this consignment is the British steamer "MARIAN MOLLER". We are advised that she is due at the South West India Dock, London, on June 26th, and will probably sail on Tuesday, 29th June. With regard to your letter of the 17th Inst, we confirm that the Bill of Lading should be made out in the name of Tomas, Miners' Union, Gijon. With best wishes. Yours sincerely, International Department. 292/946/29/125